Pr-favoured variants of the bacteriophytochrome from the plant pathogen Xanthomonas campestris hint on light regulation of virulence-associated mechanisms - Conforte, Valeria Paola (2021)
Red/far-red light-sensing bacteriophytochrome photoreceptor (BphP) pathways play key roles in bacterial physiology and ecology. These bilin-binding proteins photoswitch between two states, Pr (red absorbing) and Pfr (far-red absorbing). The isomerization of the chromophore and the downstream structural changes result in the light signal transduction. The agricultural pathogen Xanthomonas campestris pv. campestris (Xcc) code for a single bathy-like type BphP (XccBphP), previously shown to negatively regulate several light-mediated biological processes involved in virulence. Here, we generated three different full-length variants with single amino acid changes within its GAF domain that affect the XccBphP photocycle favouring its Pr state: L193Q, L193N and D199A. While D199A recombinant protein locks XccBphP in a Pr-like state, L193Q and L193N exhibit a significant enrichment of the Pr form in thermal equilibrium. The X-ray crystal structures of the three variants were solved, resembling the wild-type protein in the Pr state. Finally, we studied the effects of altering the XccBphP photocycle on the exopolysaccharide xanthan production and stomatal aperture assays as readouts of its bacterial signalling pathway. Null-mutant complementation assays show that the photoactive Pr-favoured XccBphP variants L193Q and L193N tend to negatively regulate xanthan production in vivo. In addition, our results indicate that strains expressing these variants also promote stomatal apertures in challenged plant epidermal peels, compared to wild-type Xcc. The findings presented in this work provide new evidence on the Pr state of XccBphP as a negative regulator of the virulence-associated mechanisms by light in Xcc.